PKM Kelompok Remaja SMPN 163 Jakarta dan UPBK Unindra: Penggunaan Art Therapy Sebagai Media Ekspresi Emosi - Evi Fitriyanti; Sisca Folastri; Ferry Ferry (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2020)
Emotions are very supportive in the life of every individual, whether they are positive emotions or negative emotions. The importance of individuals managing emotions in life because someone who is emotionally capable will be able to know and handle their own feelings well, the ability to manage emotions is communicated precisely one of them through art therapy. This activity provides (WPKNS) insights, knowledge, skills, values, and attitudes possessed by BK SMPN 163 Jakarta teachers and UNINDRA UPBK Students in providing useful services to clients. The activities carried out by lecturing, question and answer, discussion and practice of using art therapy. The results of the evaluation of activities that have been carried out revealed that art therapy activities are successful and provide benefits to individuals in directing and managing emotions positively. This can be seen from the enthusiasm and participation of participants during art therapy activities.